Teachers' Perceptions of a Chatbot's Role in School-based Professional Learning - Beyer Steven; Arndt Kerstin (De Gruyter, 2024)
This article focuses on the gap in research concerning the insufficient availability of information and communication technologies for teacher professional learning (TPL) and the consequent scarcity of research on technology acceptance (TA) in TPL. These research gaps are addressed through the implementation of a chatbot designed to support school-based TPL activities. Mathematics teachers and teacher training facilitators (n = 11) were interviewed regarding their TA after testing the chatbot, as a crucial factor for its implementation. The chatbot was developed to assist teachers in structuring planning tasks and facilitating the exploration and application of well-prepared knowledge. Results from qualitative content analysis indicate that this presumed potential of the chatbot can be considered confirmed in the present context. Additionally, four external variables were identified as key evaluation factors, with Perceived Quality standing out as the main reference point for Perceived Usefulness.